Ethnicity and ethnic identity in Sarawak - Jehom, Welyne Jeffrey (Universiti Kebangsaan Malaysia, 1999)
Ethnicity and ethnic identity are difficult subjects and highly problematic. This paper is a modest attempt to discuss the problem of ethnicity and ethnic identity of the diverse ethnic group, ethnicity and identity, followed by a detailed discussion of the problematic of ethnic classification and ethnic identities of Sarawakians. It suggests that authority-defined identiy, i.e., ethnic identity imposed by those in authority (such as through population census) upon a particular group need not necessarily correspond with the everyday-defined identity members of the group have of themselves. It argues among ethnic groups since it is through their interactions identities are constructed, reconstructed and reinforced.